Context-dependent group size: effects of population density, habitat, and season. (5th July 2021) - Webber, Quinn M R; Vander Wal, Eric
Abstract: Group size can vary in relation to population density, habitat, and season. Habitat and season may also interact with population density and affect group size through varying foraging benefits of social aggregation in different ecological contexts. We tested the hypothesis that group size varies across ecological contexts, including population density, habitat type, and season, for woodland caribou ( Rangifer tarandus ) in ten herds over 25 years in Newfoundland, Canada. We predicted that group size would increase as a function of population density. Based on the foraging benefits of social aggregation, we predicted larger groups as habitat openness increased because open areas tend to have higher quality foraging resources. We predicted larger groups during winter when foraging resources are covered in snow because caribou and other social animals exploit social information about the location of foraging resources. In contrast to our prediction, group size decreased as a function of population density. In support of our prediction, group size was larger in winter than calving and summer, and we found that group size increased with habitat openness in some, but not all, cases. Patterns of animal grouping are context-dependent and the additive effect of different ecological contexts on variation in group size informs our understanding of the implicit trade-offs between competition, predation risk, and profitability of forage. Abstract : Animal groups contribute to the social environment. The profitability of the social environment changes with ecological context, and may be reflected in changing group sizes. For example, population density, habitat, and season are important contexts across which group sizes may vary. We tested how ecological context could affect group size in caribou. We found that group size decreased with increasing population density, groups were larger in winter and that groups increased in size across habitat openness. Articulating context-dependent trends in group size lends precision to understanding how ecological context shapes the social environment.